Impact of COVID-19 on corneal endothelial density and morphology: a cross-sectional study in convalescent patients - Ling Zhang; Wenjian Shi; Xiumei Guo; Runhua Lv; Huilin Guan; Feng Zheng; Yingying Gao (Frontiers in Medicine, 2026)
Aim This study aimed to investigate the effect of COVID-19 infection on corneal endothelial cell density and morphology, and to analyze the related factors. Methods This cross-sectional study included patients who underwent corneal endothelial examination at our institute from August 2022 to May 2023. Patients were categorized into COVID-19 recovery group and non-COVID-19-infection group according to their SARS-CoV-2 infection history. Endothelial cell density (ECD), s tandard deviation of cell area (SD-Area), average cell area (ACA), and hexagonal cell percentage (HEX), among others, were compared between the two groups. To account for confounding factors, univariate analysis assessed the relationship between COVID-19 infection, demographics, medical history, and corneal endothelial cell characteristics. Subsequently, multiple linear regression pinpointed independent factors linked to cell density and morphology. Results Three hundred seventy-eight patients recovering from COVID-19 and 382 individuals without a history of COVID-19 infection were included in the study. Analysis of corneal endothelial parameters demonstrated a statistically significant decrease in ECD ( p < 0.001) and HEX ( p = 0.005) in the COVID-19 recovery group compared to the non-COVID-19 infection group. Additionally, higher SD-Area ( p < 0.001), increased ACA ( p < 0.001), and greater MAX ( p < 0.001) were observed in the COVID-19 recovery group. Multiple linear regression analysis suggested that COVID-19 infection history and advanced age were independent factors associated with decreased corneal endothelial density and irregular morphology. Conclusion A history of COVID-19 infection was found to be significantly associated with decreased corneal endothelial cell density and altered morphology in convalescent patients. While these findings suggest potential long-term ocular surface implications, further prospective studies with pre-infection baselines are warranted to establish causality and to define specific, evidence-based guidelines for perioperative corneal endothelial protection in this population.